Metabolic underpinnings of leukemia pathology and treatment. Issue 2 (7th October 2018) - Nemkov, Travis; D'Alessandro, Angelo; Reisz, Julie A.
Abstract: Background: Carcinogenic transformation of white blood cells during hematopoiesis leads to the development of leukemia, a cancer characterized by incompetent immune cells and a disruption of normal bone marrow function. Leukemias are diverse in type, affected population, prognosis, and treatment regimen, yet a common theme in leukemia is the dysregulated metabolism of leukemic cells and leukemic stem cells with respect to their noncancerous counterparts. Recent findings: In this review, we highlight current findings that elucidate metabolic traits unique to the four major types of leukemia, which confer carcinogenic survival but can be potentially exploited for therapeutic intervention. These metabolic features can work in conjunction with or be independent of unique aspects of the bone marrow microenvironment that can also influence cell survival and proliferation, thus sustaining carcinogenesis. Conclusion: Deepening our understanding of the interactions of leukemias with their niche environments in vivo will inform future treatments for leukemia, particularly for those that are refractive to tyrosine kinase inhibitors and other therapeutic mainstays.